Microbial lipase production optimization, characterization and application in coconut oil modification - Khoramnia, Anahita (2012)
Lipases are the enzymes that catalyze the hydrolysis of fats and oils and can be found widely in nature. These lipases, especially when from microbial sources are preferred and extensively used especially in biotechnological applications and commercial industries. Nowadays, the use of antibiotics have been thought to contribute to the emergence of antibiotic-resistant microorganisms and a new market for natural food additives with antimicrobial properties has been opened. One of the most popular elements with strong anti microbial activities are medium-chain fatty acid glycerides and mediumchain free fatty acids (MCFA) particularly lauric acid. Coconut oil is considered as a good source of MCFA as it consisted of about 50% lauric acid in triglyceride form. Medium chain triglycerides (MCTGs) could be hydrolyzed to medium chain glyceride derivatives and MCFAs including lauric acid using lipases. Therefore, in this study bacterial and fungal lipases were produced, optimized and characterized. Certain possible applications in coconut oil modification were also investigated. Different fermentation systems were also developed to get the highest lipolytic activity and functionality in coconut oil modification. Among different lipase producing bacterial isolates, three Gram-positive cocci (Staphylococcus xylosus, S. sciuri, S. aureus) and one Gram-negative short rod (Acinetobacter sp.) were selected based on their highest lipase production activity and better lipase characteristics. Bacterial isolates were found to be new strains according to the BIOLOG and DSMZ identification. All strains were able to produce lipase in submerged fermentation (SmF) but only Acinetobacter sp. showed the same capability on coconut solid state fermentation (SSF). The use of fungi for the production of commercially important products has increased rapidly over the past half century. Two lipolytic filamentous fungal strains, Geotrichum candidum ATCC 34614 and G. candidum local isolate were investigated in the case of lipase production in both SmF and SSF. Lipase production for G.candidum ATCC 34614 was 15 times higher than the bacterial isolates while, for the local strain it was in the same range with bacterial isolates. Both fungal strains revealed great potential on coconut SSF. Modeling studies on culture parameters optimization for lipase production of these microorganisms were performed using response surface methodology (RSM) and artificial neural networks (ANNs). Based on the obtained optimum conditions,lipases were produced in SmF for characterization studies. The results demonstrated good characteristics for all lipases as they were found to be thermostable, acid-base tolerant and solvent-detergent stable. Lipases were then used to perform hydrolysis reaction on coconut oil. A coconut solid-state fermentation system was developed in order to apply the produced lipase directly on substrate without any downstream processing. Both fungal strains SSF lipases showed high functionality on coconut oil MCTG conversion into MCDG, MCMG and MCFA. The oil conversion percentages reached to 78% and 76% after optimization for G. candidum ATCC 34614 and G. candidum local strain, respectively. The local strain showed higher lipase functionality under extreme conditions of moisture and oil content compared to the former strain that revealed no activity in those conditions. Microscopic studies demonstrated that the local strain can grow faster and better on coconut solid culture with penetration capability compared to G. candidum ATCC 34614. Coconut oil was successfully modified by G. candidum lipases under solid state fermentation of coconut. The bacterial strain (Acinetobacter sp.) did not reveal any activity in coconut oil modification due to its short shelf life on coconut solid culture. Modified coconut oils obtained from direct fermentation of fungal lipase during SSF process were characterized for its antimicrobial activity and thermal characteristics. The optimized modified coconut oils extracted from G. candidum ATCC 34614 and G. candidum local strain revealed 95 and 90 % antimicrobial activity against S.aureus and 90 and 85% against E. coli, respectively. The contributions of high level lauric acid together with medium chain mono- and di- glycerides in modified coconut oils were the key factors for antimicrobial activity. The solid and submerged fermented coconuts also showed bactericidal effects. Differential scanning calorimetry of modified coconut oils showed lower melting points compared to the normal coconut oil. G. candidum ATCC 34614 cultures analysis using HS-SPME/GC-MS also showed that 46 and 37 aromatic compounds were produced during the SmF and SSF, respectively. The produced aromatic compounds were mainly esters with fruity and flora notes in the modified coconut samples indicating successful hydrolysis of the lipases.